G-Quadruplexes Formation at the Upstream Region of Replication Origin (OriL) of the Pseudorabies Virus: Implications for Antiviral Targets - Yance Zhu (MDPI AG, 2021)
Pseudorabies virus (PRV) is the causative agent of Aujeszky’s disease, which still causes large economic losses for the swine industry. Therefore, it is urgent to find a new strategy to prevent and control PRV infection. Previous studies have proven that guanine (G)-rich DNA or RNA sequences in some other viruses’ genomes have the potential to form G-quadruplex (G4), which serve as promising antivirus targets. In this study, we identified two novel G4-forming sequences, OriL-A and OriL-S, which are located at the upstream origin of replication (OriL) in the PRV genome and conserved across 32 PRV strains. Circular dichroism (CD) spectroscopy and a gel electrophoresis assay showed that the two G-rich sequences can fold into parallel G4 structures in vitro. Moreover, fluorescence resonance energy transfer (FRET) melting and a Taq polymerase stop assay indicated that the G4 ligand PhenDC3 has the capacity to bind and stabilize the G4. Notably, the treatment of PRV-infected cells with G4-stabilizer PhenDC3 significantly inhibited PRV DNA replication in host cells but did not affect PRV’s attachment and entry. These results not only expand our knowledge about the G4 characteristics in the PRV genome but also suggest that G4 may serve as an innovative therapeutic target against PRV.